Assessment of the Clavien‐Dindo classification system for complications in head and neck surgery. (27th September 2014) - Monteiro, Eric; Sklar, Michael C.; Eskander, Antoine; de Almeida, John R.; Shrime, Mark; Gullane, Patrick; Irish, Jonathan; Gilbert, Ralph; Brown, Dale; Higgins, Kevin; Enepekides, Danny; Goldstein, David P.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The importance of reporting and grading surgical complications is central to quality improvement in head and neck surgery. The purpose of this study is to assess the interobserver reliability, content validity, and construct validity of the Clavien‐Dindo classification system for use in grading complications related to head and neck surgery. Study Design 1 and 2. Methods Hypothetical cases of common head and neck surgical complications, along with a brief questionnaire, were responded to by 81 residents, fellows, and head and neck surgeons for grading to assess the interobserver reliability of the Clavien‐Dindo system. Construct validity was assessed with the a priori hypothesis that increasing complication grade resulted in an increased length of hospital stay. Results Interobserver reliability scores for the complication grading scenarios ranged mostly from moderate to high. The grading system was well received by the respondents, but specific concerns were raised regarding utility in head and neck surgery. Construct validity was confirmed as hospital length of stay was statistically related to complication grade (P = .002) Conclusion Reporting of complications is critical to quality improvement in surgical practice. Currently, the Clavien‐Dindo complication grading scale system is a useful tool for grading head and neck surgery complications; however, the development of a grading scale customized to head and neck surgery may be beneficial in the future. Level of Evidence N/A. Laryngoscope, 124:2726–2731, 2014